E‐BEST Principles: Infusing Technology Into the Writing Workshop. (23rd August 2013) - Coskie, Tracy L.; Michelle Hornof, M.
Abstract: As teachers work to move their writing workshop into the 21st century and to help students meet new standards expectations, they are ramping up their use of technology. This article lays out a set of guiding principles (E‐BEST) to help teachers make reflective choices, so that the digital technologies in their workshops will enhance and extend student learning.